2008
DOI: 10.1007/s10260-007-0086-0
|View full text |Cite
|
Sign up to set email alerts
|

Estimating and using propensity score in presence of missing background data: an application to assess the impact of childbearing on wellbeing

Abstract: Ignorability, Propensity score, Missing data, Childbearing, Wellbeing,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 17 publications
1
75
0
Order By: Relevance
“…Although a low proportion of missing data was observed in our study (4.0%), a multiple imputation (i.e., five simulations) was performed to handle missing background data in the estimation and the use of the propensity scores (Supporting Information) …”
Section: Methodsmentioning
confidence: 99%
“…Although a low proportion of missing data was observed in our study (4.0%), a multiple imputation (i.e., five simulations) was performed to handle missing background data in the estimation and the use of the propensity scores (Supporting Information) …”
Section: Methodsmentioning
confidence: 99%
“…It is important to note, that although our study is cross-sectional, these methods have recently been suggested as a means of accounting for missing data values in longitudinal analysis [26]. The basic idea is that separate PSs are computed for subsets of subjects with different missing information patterns.…”
Section: Resolutions Of Problemsmentioning
confidence: 99%
“…Note that an alternative approach would be to define Xobs instead as RX (which is equivalent to X) and Xmis as (1R)X. However, for the purposes of this paper, we use the Xobs and Xmis notation, following the literature on which our theory builds (D'Agostino & Rubin, ; Mattei, ).…”
Section: Introductionmentioning
confidence: 99%
“…We call the second and third assumptions the conditionally independent treatment (CIT) assumption and the conditionally independent outcomes (CIO) assumption, respectively. The CIT assumption is that missing confounder values are conditionally independent of treatment, given the observed confounder values and the missing indicator, whereas the CIO assumption is that missing confounder values are conditionally independent of the potential outcomes (Mattei, ). truerightnormalCIT:1emZleftXmis|C,Xobs,R. truerightnormalCIO:1emYfalse(zfalse)leftXmis|C,Xobs,R1emnormalforz=0,1. Note that in scenarios with partially observed confounders, the mSITA, CIT, and CIO assumptions replace the SITA assumption with respect to identification of the causal estimand.…”
Section: Introductionmentioning
confidence: 99%